Analisis in silico senyawa bioaktif kesambi (Schleichera oleosa) sebagai kandidat anti-gastritis: Evaluasi drug-likeness, farmakokinetik ADMET, dan interaksi molekuler terhadap target H⁺/K⁺-ATPase - JANNAH, ELOK WARDATUL (Maliki Interdisciplinary Journal, 2026)
Gastritis is an inflammatory disorder of the gastric mucosa with an increasing prevalence worldwide. The primary treatment for gastritis commonly involves Proton Pump Inhibitors (PPIs); however, their long-term use may cause various adverse effects, highlighting the need for safer therapeutic alternatives. This study aimed to evaluate the potential of bioactive compounds from kesambi (Schleichera oleosa) as candidates for H⁺/K⁺-ATPase proton pump inhibition through an in silico approach. Active compounds were identified using Liquid Chromatography–Mass Spectrometry (LC-MS), followed by bioactivity prediction using PASS Online. Drug-likeness and pharmacokinetic properties were assessed using SwissADME, while molecular docking analyses were performed using PyRx and BIOVIA Discovery Studio to investigate ligand–protein interactions. The evaluated parameters included binding affinity, Root Mean Square Deviation (RMSD), ADMET profiles, and ligand–protein interaction patterns. The analysis is expected to identify bioactive compounds from S. oleosa with strong binding affinity, favorable pharmacokinetic characteristics, and potential inhibitory activity against H⁺/K⁺-ATPase. These findings may provide a scientific basis for the development of S. oleosa-derived bioactive compounds as natural anti-gastritis agents that act through the inhibition of gastric proton pumps.